Loss‐of‐function variants in ARHGEF9 are associated with an X‐linked intellectual disability dominant disorder. Issue 5 (14th March 2021) - Ghesh, Leïla; Besnard, Thomas; Nizon, Mathilde; Trochu, Eva; Landeau‐Trottier, Gaëlle; Breheret, Flora; Thauvin‐Robinet, Christel; Bruel, Ange‐Line; Kuentz, Paul; Coubes, Christine; Cuisset, Laurence; Mignot, Cyril; et al.
Abstract: ARHGEF9 defects lead to an X‐linked intellectual disability disorder related to inhibitory synaptic dysfunction. This condition is more frequent in males, with a few affected females reported. Up to now, sequence variants and gross deletions have been identified in males, while only chromosomal aberrations have been reported in affected females who showed a skewed pattern of X‐chromosome inactivation (XCI), suggesting an X‐linked recessive (XLR) disorder. We report three novel loss‐of‐function (LoF) variants in ARHGEF9 : A de novo synonymous variant affecting splicing (NM_015185.2: c.1056G>A, p.(Lys352=)) in one female; a nonsense variant in another female (c.865C>T, p.(Arg289*)), that is, also present as a somatically mosaic variant in her father, and a de novo nonsense variant in a boy (c.899G>A; p.(Trp300*)). Both females showed a random XCI. Thus, we suggest that missense variants are responsible for an XLR disorder affecting males and that LoF variants, mainly occurring de novo, may be responsible for an X‐linked dominant disorder affecting males and females. Abstract : ARHGEF9 defects lead to an X‐linked intellectual disability disorder related to inhibitory synaptic dysfunction. This condition is more frequent in males, most of whom are carriers of inherited missense variants. This study describes de novo loss‐of‐function variants in two affected females and one male.